Ethical Boundaries Of Artificial Intelligence Use In Academic Writing: A Study Among University Students - Muhammad Dzaky Nabil Al Ghani; Zidni Ma’ruf; M. Kurniawan Aries Akbar; Muhammad Akbar (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2026)
As Artificial Intelligence (AI) becomes increasingly common in higher education, worries regarding academic honesty and ethical standards have increased. This study intends to explore how university students view and apply ethical limits while utilizing AI tools for academic writing. A group of six undergraduate students at Politeknik Negeri Sriwijaya, who have experience using AI assistants, were interviewed through semi-structured interviews using a qualitative descriptive design. The study reveals that students perceive AI as a supporter of brainstorming, idea generation, and structural validation, rather than removing human intellect altogether. A clear ethical limit is established, and the use of AI is considered unethical if it necessitates unreviewed